Lithium Recovery From Lapindo Sludge Water (Brine) By Adsorption Method Using Manganese Dioxide (Mno2) Adsorbent - Adinda Nurkholisha; R.A. Elisa Eka Purnamasari (Green Publisher Indonesia, 2025)
This article discusses the recovery of lithium from Lapindo sludge water in Sidoarjo using the adsorption method with Manganese Dioxide (MnO2) adsorbents. This study aims to determine the optimal lithium recovery rate based on variations in stirrer speed and adsorbent concentration. The results of the analysis showed that the stirring speed of 150 rpm with an adsorbent concentration of 2.5 g/L gave the highest lithium recovery result, which was 53.2 ppm. In addition, the adsorption process follows the Freundlich model, showing that the adsorbent has a good capacity to bind lithium from the solution. This research provides new insights into the use of sludge water as an alternative source of lithium in Indonesia.